The Bad Guys 2 [videorecording (DVD)] - Brenner, Yoni; Cohen, Etan; Pemberton, Daniel; Blabey, Aaron (Dreamworks, Universal, 2025)
The Bad Guys are struggling to find trust and acceptance in their newly minted lives as Good Guys, when they are pulled out of retirement and forced to do "one last job" by an all-female squad of criminals. Everyone, including The Crimson Paw, is being blackmailed by the girls, and their only way out may be an old nemesis.